P09.23 Immune cell infiltration as a novel marker for predicting patient outcome in nephroblastoma. (21st September 2022) - Watzke, L; Sorger, H; Palmisani, F; Metzelder, M; Amann, G; Bergmann, M
Abstract : Background: Gaining insights into the tumor microenvironment (TME) of adult cancers improved clinical outcome and enabled newlines of therapies for these patients. In pediatric cancers, which are known tohave less extensive immune infiltrates, little is known about the TME. Innephroblastoma, with a 5-year survival rate of 80–90%, investigating the TMEmay hold the key to further improve patient prognosis and risk stratification. Materials and Methods: In aretrospectivestudy including 110 patients with renal tumors treated according to the SIOPtherapy protocol, we immunohistochemically stained formalin fixed, paraffinembedded slides of nephroblastoma specimen for T-cell, B-cell, NK-cell andmacrophage markers (CD4, CD8, CD20, CD57, CD68). Quantification and comparisonbetween different histologic regions (epithelial, blastemal and mesenchymal) aswell as immune cell infiltration analysis was done using HALO AI by indica labs. Results: Out of the three histologicregions of nephroblastoma, the highest concentrations of T-cells andmacrophages were found in mesenchymal regions (CD68 + : 1884, 70 cellsper mm 2 and CD8 + : 58, 76 cells per mm 2 ), the least in blastemalregions (CD68 + : 662, 31 cells per mm 2 and CD8 + : 4, 48 cellsper mm 2 ). Concentrations in epithelial regions were found to be in between(CD68 + : 1560, 16 cells per mm 2 and CD8 + : 19, 96 cells permm 2 ). Furthermore, overall immune infiltrates of T-cells and macrophages werelowest in patients experiencing tumor relapse (4/85 nephroblastoma patients) ormetastasis (9/85 nephroblastoma patients) (p-values for overall relapse vs. norelapse, were 0.0004 in CD68 + cells and 0.016 in CD8 + cells). Conclusions: Lowest immune infiltrates ofT-cells and macrophages are found in the more stem cell like blastemal regionsof nephroblastoma as compared to epithelial and mesenchymal regions. Overalllow immune cell infiltrates of T-cells and macrophages are associated with aworse patient prognosis. Taken together this data could provide a tool for riskgroup stratification and improve therapy outcome. Disclosure Information: L. Watzke: None. H. Sorger: None. F. Palmisani: None. M. Metzelder: None. G. Amann: None. M. Bergmann: None.